The overexpression of a single oncogene (ERBB2/HER2) alters the proteomic landscape of extracellular vesicles. Issue 12 (15th May 2014) - Amorim, Maria; Fernandes, Gustavo; Oliveira, Paulo; Martins‐de‐Souza, Daniel; Dias‐Neto, Emmanuel; Nunes, Diana
<x xml:space="preserve">Abstract</x> ERBB2/HER2 amplification activates signaling cascades that lead to a tumor cell phenotype. However, despite its remarkable importance in oncology, the consequences of HER2 amplification over the extracellular vesicles (EVs) content have not yet been investigated. Here, we isolated EVs secreted by HB4a, a mammary luminal epithelial cell line and C5.2, its HER2‐overexpressing clone. We isolated two EV sets (20 and 100 K) by ultracentrifugation and used electron microscopy and nanoparticle tracking analysis for their morphological characterization. We employed GeLC‐MS/MS combined with isotope‐coded protein labeling to evaluate cell‐derived proteins and LC‐MS/MS label free spectral counting to quantify the EVs proteome. We found higher HER2 levels in both C5.2‐derived EVs when compared with C5.2 cells, suggesting its preferential shuttling. Proteins capable of inducing malignant transformation are enriched in both C5.2 EV subsets, including two HER2‐related proteins involved in cell motility and invasion, cofilin and CD44. MetaCore™ analysis indicated an enrichment of cell adhesion and cytoskeleton‐remodeling pathways in C5.2 EVs, as well as proteins related to HER2 signaling, such as sphingosine‐1‐phosphate pathway. Together, our data indicate that in terms of protein content, distinct vesicle sets reinforce and complement each other. Our results also suggest that HER2‐upregulated proteins from EVs may be relevant for cellular malignancy and can be potential biomarkers for HER2+ cancer patients.